Characterization of transgenic wheat lines expressing maize ABP7 involved in kernel development - Zaid CHACHAR; Siffat Ullah KHAN; Xu-huan ZHANG; Peng-fei LENG; Na ZONG; Jun ZHAO (Journal of Integrative Agriculture)
Wheat is one of the major food crops in the world. Functional validation of the genes in increasing the grain yield of wheat by genetic engineering is essential for feeding the ever-growing global population. This study investigated the role of ABP7, a bHLH transcription factor from maize involved in kernel development, in regulating grain yield-related traits in transgenic wheat. Molecular characterization showed that transgenic lines HB123 and HB287 contained multicopy integration of ABP7 in the genome with higher transgene expression. At the same time, QB205 was a transgenic event of single copy insertion with no significant difference in ABP7 expression compared to wild-type (WT) plants. Phenotyping under field conditions showed that ABP7 over-expressing transgenic lines HB123 and HB287 exhibited improved grain yield-related traits (e.g., grain number per spike, grain weight per spike, thousand-grain weight, grain length, and grain width) and increased grain yield per plot, compared to WT plants, whereas line QB205 did not. In addition, total chlorophyll, chlorophyll a, chlorophyll b, and total soluble sugars were largely increased in the flag leaves of both HB123 and HB287 transgenic lines compared to the WT. These results strongly suggest that ABP7 positively regulates yield-related traits and plot grain yield in transgenic wheat. Consequently, ABP7 can be utilized in wheat breeding for grain yield improvement.